Affiliator Judi Online Dalam Perspektif Hukum Positif Indonesia - Hafida Aristya Arditha (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The progress of information technology in Indonesia is very fast. With this rapid progress, it is not matched by progress in the knowledge and mentality of the community, and this very significant progress is used by some people to conduct destructive business, namely the online gambling business. Online gambling itself is a problem in society that is said to have a very negative effect and must be dealt with thoroughly. So the regulations regarding the creation of gambling sites and people who promote these sites in the media are regulated in the law, namely the ITE Law. This research uses normative legal methods with literature study data collection techniques, which results in online gambling having a negative effect on various social values, and perpetrators who promote online gambling can be subject to criminal charges.